Changing economic structures and impacts of shocks: evidence from a DSGE for China - Aaron Mehrotra; Riikka Nuutilainen; Jenni Pääkkönen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
We construct a small-scale dynamic stochastic general equilibrium (DSGE) model that features price rigidities, habit formation in consumption and costs in capital adjustment, and calibrate the model with data for the Chinese economy. Our interest centers on the impact of technology and monetary policy shocks for different structures of the Chinese economy. In particular, we evaluate how a rebalancing of the economy from investment-led to consumption-led growth would affect the economic dynamics after a shock occurs. Our findings suggest that a rebalancing would reduce the volatility of the real economy in the event of a technology shock, which provides support for policies aiming to increase the consumption share in China.
URN:NBN:fi:bof-201408071928
Keywords: E52; E60; 330; DSGE; rebalancing; monetary policy shocks; technology shocks; China